2003
DOI: 10.1149/1.1571531
|View full text |Cite
|
Sign up to set email alerts
|

Mg Intercalation Properties into V[sub 2]O[sub 5] gel/Carbon Composites under High-Rate Condition

Abstract: V 2 O 5 /carbon composites were prepared from a homogeneous suspension in which vanadium pentoxide sol and acetylene black powder were mixed with acetone acting as a surfactant. The composite was loaded on indium-tin oxide ͑ITO͒-coated glass, and then the magnesium intercalation property and the high-rate charge-discharge performance were evaluated in an electrolyte of Mg(ClO 4 ) 2 /acetonitrile at room temperature. In cyclic voltammetry, two main peaks of a reversible redox reaction were observed. It was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
107
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 13 publications
12
107
0
Order By: Relevance
“…On comparing the charge-discharge curves before and after the 15th cycle (Figures 1a and 1b), it was found that the typical electrochemical behavior of the cell, with a significant plateau (Figure 1a), gradually changes to a sloped discharge-charge voltage curve (Figure 1b), indicating that a complex reaction occurs during the Mg 2 þ insertion and extraction, which is different from the changes in Li þ /Na þ storage in LTO. Figure 1c shows that the reversible capacity becomes lower at high current rates than at low current rates, implying that Mg diffusion in the host has relatively sluggish kinetics, [15][16][17][18] which are related to the high polarizing power of a divalent Mg cation and further proven by the fact that larger LTO NPs (e.g., 15-20 nm) deliver a much lower specific capacity (Supplementary Figure S4) than the LTO NPs in this work (ca. 7-8 nm).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…On comparing the charge-discharge curves before and after the 15th cycle (Figures 1a and 1b), it was found that the typical electrochemical behavior of the cell, with a significant plateau (Figure 1a), gradually changes to a sloped discharge-charge voltage curve (Figure 1b), indicating that a complex reaction occurs during the Mg 2 þ insertion and extraction, which is different from the changes in Li þ /Na þ storage in LTO. Figure 1c shows that the reversible capacity becomes lower at high current rates than at low current rates, implying that Mg diffusion in the host has relatively sluggish kinetics, [15][16][17][18] which are related to the high polarizing power of a divalent Mg cation and further proven by the fact that larger LTO NPs (e.g., 15-20 nm) deliver a much lower specific capacity (Supplementary Figure S4) than the LTO NPs in this work (ca. 7-8 nm).…”
Section: Resultsmentioning
confidence: 67%
“…[7][8][9] In particular, the increasing attention to rechargeable Mg batteries is due to the pioneering work of Aurbach's group. [10][11][12][13][14] Some progress has been achieved toward designing electrode materials 10,[15][16][17][18][19][20][21][22][23][24] and electrolytes [25][26][27][28][29] for rechargeable Mg batteries. Nevertheless, rechargeable Mg batteries are still in their infancy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some authors reported that vanadium bronzes [5,6], graphite fluorides [7] and transition metals oxides [6,8,9] may intercalate magnesium, and thus they may be considered as electrode materials for secondary Mg--ion batteries. However, on the present level of knowledge, such a type of battery suffers of two unresolved problems, the first one being the passivation of metallic magnesium if used as anode in commonly used organic electrolytes, and the second one being low capacity utilization during the Mg-intercalation process [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…By an analogous procedure enlarged by addition of acetylene black, composite V 2 O 5 /C can be synthesised. There exist the literature data that in organic electrolyte solutions, both lithium and manganese ions may be reversibly intercalated into V 2 O 5 /C composite at an acceptably high rate [11,16,17]. However, similar examinations in aqueous solutions were not published thus far.…”
Section: Introductionmentioning
confidence: 99%
“…39 The initial capacity was about 80 mAh/g with a slope voltage profi le averaged at 0.5 V. Imamura et al prepared V 2 O 5 /carbon composition and obtained a high initial capacity up to 550 mAh/g in a three-electrode cell using 1 M Mg(ClO 4 ) 2 /acetonitrile electrolyte. 40 Imamura et al further studied the structural evolution upon magnesiation/demagnesiation process through x-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) techniques, which clearly identifi ed the intercalation of Mg 2+ ion in the layered structure. 41 Recent work by Aurbach's group on V 2 O 5 significantly advanced our understanding of this cathode material in Mg battery system.…”
Section: Oxide Cathodesmentioning
confidence: 99%